Clonality of neutrophilia associated with plasma cell neoplasms: report of a SETBP1 mutation and analysis of a single institution series. Issue 4 (2nd April 2016) - Stevens, Brett; Maxson, Julia; Tyner, Jeffrey; Smith, Clayton A.; Gutman, Jonathan A.; Robinson, William; Jordan, Craig T.; Lee, Choon-Kee; Swisshelm, Karen; Tobin, Jennifer; Wei, Qi; Schowinsky, Jeffrey; et al.
Abstract: A rare but well-known association between plasma cell neoplasms and neutrophilia is known to exist. Whether the neutrophilia is secondary to the plasma cell neoplasm or this convergence represents two independent clonal disorders is unclear. We reviewed five consecutive cases from a single institution over a 3-year period, applying molecular, cytogenetic and cytokine-profiling approaches to determine whether neutrophilia associated with plasma cell neoplasms represents a reactive or clonal process. We report, for the first time, the occurrence of a SETBP1 mutation in two cases, as well as changes in G-CSF and IL-6 in SETBP1 wild type vs. mutated patients that are supportive of a hypothesis that neutrophilia associated with plasma cell neoplasms may sometimes be reactive and may sometimes represent a second clonal entity. Finally, using an ex vivo drug screening platform we report the potential efficacy of the multi-kinase inhibitor dasatinib in select patients.